2020
DOI: 10.2174/2405520413666200313130911
|View full text |Cite
|
Sign up to set email alerts
|

The Opportunities and Challenges of Preformed Particle Gel in Enhanced Oil Recovery

Abstract: Enhanced Oil Recovery (EOR), is a technique that has been used to recover the remaining oil from the reservoirs after primary and secondary recovery methods. Some reservoirs are very complex and require advanced EOR techniques that containing new materials and additives in order to produce maximum oil in economic and environmentally friendly manners. Because of EOR techniques, in this work previous and current challenges have been discussed, and suggested some future opportuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Several gel systems have been developed for oil reservoirs with different conditions, including particle gels, gel agents that have excellent salt resistance, solvent–polymer weak gels, colloidal dispersion gels, and an ultrahigh molecular weight-hydrolyzed polyacrylamide (HPAM)/phenolic weak gel system, which effectively expand the applicability and potential of weak gels. Furthermore, the combination of weak gels and microorganisms, as well as the CO 2 –gel fracturing system in shale oil reservoirs, is a new trend. , However, the flow properties of weak gel systems in porous media are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several gel systems have been developed for oil reservoirs with different conditions, including particle gels, gel agents that have excellent salt resistance, solvent–polymer weak gels, colloidal dispersion gels, and an ultrahigh molecular weight-hydrolyzed polyacrylamide (HPAM)/phenolic weak gel system, which effectively expand the applicability and potential of weak gels. Furthermore, the combination of weak gels and microorganisms, as well as the CO 2 –gel fracturing system in shale oil reservoirs, is a new trend. , However, the flow properties of weak gel systems in porous media are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…This results in the formation of a polymer gel of specified strength in a high-permeability zone away from the injector, which then forces the fluid to move into a low-permeability zone with high oil saturation, expanding the sweep volume and improving oil displacement efficiency. 23,24 Several gel systems have been developed for oil reservoirs with different conditions, including particle gels, gel agents that have excellent salt resistance, solvent−polymer weak gels, colloidal dispersion gels, and an ultrahigh molecular weight-hydrolyzed polyacrylamide (HPAM)/phenolic weak gel system, 23−27 which effectively expand the applicability and potential of weak gels. Furthermore, the combination of weak gels and microorganisms, as well as the CO 2 −gel fracturing system in shale oil reservoirs, is a new trend.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Field studies indicated that the synthesis approach of hydrogels, salt solution properties (including the salt type and concentration and pH of the solution), and environmental properties where PPGs are placed (including temperature and pressure of the medium) can affect the PPG performance. , Imran et al discussed the challenges existing in environmentally and economically producing oil from reservoirs including undesirable water channels. They concluded that conformance control, PPG transportation, and surface wettability are deciding factors affecting PPG efficiency.…”
Section: Introductionmentioning
confidence: 99%